Lymphomonocytic inflammatory infiltrate with numerous eosinophilic granulocytes in the interstitium in a surviving heart transplant recipient: a case report - Placidi, Silvia; Francalanci, Paola; Adorisio, Rachele; Girardi, Katia; Vinti, Luciana; Panebianco, Mario; Rebonato, Micol; Amodeo, Antonio; Grutter, Giorgia (Frontiers in Cardiovascular Medicine, 2024)
Findings of eosinophilic and lymphomonocytic inflammatory infiltrates in endomyocardial biopsies (EMBs) may help in myocardial disease diagnosis identification. Eosinophilic myocarditis (EM), a rare condition, is fatal if left untreated and has rarely been described in heart transplant recipients. An extensive work up is necessary to achieve an early etiological diagnosis; however, the underlying cause remains unexplained in nearly one-third of the patients. The cornerstone of treatment is corticosteroids, comprehensive therapy and heart failure management (including advanced mechanical support for fulminant myocarditis). We have described the case of a 17-year-old heart transplant recipient who presented with a cardiogenic shock. He was admitted to our intensive care unit and treated with inotropic drugs, such as milrinone, adrenaline, vasopressin, and levosimendan; the doses of these drugs were in accordance with our internal protocol. The patient underwent cardiac catheterization, coronarography, and right ventricular EMB. EMB revealed inflammatory lymphomonocytic and eosinophil granulocyte infiltrates; thus, steroid therapy was initiated, with complete recovery achieved after 15 days. Performing an early differential diagnosis among eosinophilic infiltration, acute cellular rejection (ACR), and possible chemotherapeutic damage is emerging as an important challenge. To our knowledge, this is the first reported case of a lymphomonocytic inflammatory infiltration with numerous eosinophilic granulocytes in the interstitium in a surviving heart transplant recipient.